Hinduism, Belief and the Colonial Invention of Religion: A before and after Comparison - Ranganathan, Shyam (Religions, 2022)
As known from the academic literature on Hinduism, the foreign, Persian word, “Hindu” (meaning “Indian”), was used by the British to name everything indigenously South Asian, which was not Islam, as a religion. If we adopt explication as our research methodology, which consists in the application of the criterion of logical validity to organize various propositions of perspectives we encounter in research in terms of a disagreement, we discover: (a) what the British identified as “Hinduism” was not characterizable by a shared set of beliefs or shared outlook, but a disagreement or debate about basic topics of philosophy with a discourse on tenets of moral philosophy anchoring the debate; and (b), the Western tradition’s historical commitment to language as the vehicle of thought not only leads to the conflation of propositions with beliefs, but to interpreting (explaining by way of belief) on the basis of the Eurocentric tradition rooted exclusively in ancient Greek philosophy. Interpretation on the basis of the Western tradition leads to the Western tradition vindicating itself as the non-traditional, non-religious, rational platform—the secular—for explaining everything—the residua are what get called religions on a global scale. Given that Western colonialism is the pivotal event, before which South Asians just had philosophy, and after which they had religion (the explanatory residua of Eurocentric interpretation), we can ask about Hindu religious belief. This only pertains to the period after colonialism, when Hindus adopted a Westcentric frame for understanding their tradition as religious because of colonization. Prior to this, the tradition the British identified as “Hindu” had a wide variety of philosophical approaches to justification, which often criticized propositional attitudes, like belief, as irrational.